PENGARUH REBUSAN JINTAN HITAM DENGAN MADU TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU MENYUSUI DI DESA SIDOMULYO KABUPATEN DELI SERDANGPENGARUH REBUSAN JINTAN HITAM DENGAN MADU TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU MENYUSUI DI DESA SIDOMULYO KABUPATEN DELI SERDANG - G.F.GUSTINA SIREGAR; MUTIARA DWI YANTI (Universitas Pahlawan Tuanku Tambusai, 2021)
Breastfeeding after the baby born is the formation of quality resources. Because babies who are breastfed have better immunity and nutritional needs. However, the problem that is often found in mothers is the lack of milk after the mother gives birth. Efforts that can be made in increasing breast milk production can be done by doing breast care, breastfeeding techniques or by consuming foods that can affect breast milk production. Indonesia is a country that has many medicinal plants, including black cumin and honey. Black cumin is in the form of black seed granules which contain polyphenols which play a role in increasing prolactin and oxytocin levels. Honey increases the release of breast milk and the number of antibodies in breast milk. The research method used is an experimental method using a design before and after the intervention using one group. The research design used pre and post test design. The population in this study were all mothers who breastfeed their babies in Sidomulyo Village, Deli Serdang Regency. Sampling in this study uses the Consecutive Sampling technique, namely the researcher selects all subjects who meet the criteria until the required number of subjects is met where in this study the number of samples used was 30 people. Statistical test analysis shows that the Z value in this study is -5.844 with a sig. 0.000 <0.05, so it can be assumed that there is an effect of decoction of black cumin with honey on increasing breast milk production in breastfeeding mothers in Sidomulyo Village, Deli Serdang Regency in 2020.